The impenetrable jungle: The status of cy-près in Western Australia - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2012)
The doctrine of cy-près is a very difficult area within charity law and has been described as an ‘impenetrable jungle’. 2 Unsurprisingly, some jurisdictions have sought to simplify the law in this area by enacting legislation.